Shen-ling-bai-zhu-san ameliorates inflammation and lung injury by increasing the gut microbiota in the murine model of Streptococcus pneumonia-induced pneumonia - Jinli Feng; Weibo Dai; Cheng Zhang; Houjun Chen; Ziliang Chen; Yongfeng Chen; Qianyi Pan; Yongmao Zhou (BMC, 2020)
Abstract Background Shen-ling-bai-zhu-san (SLBZS) regulates inflammation and gut microbiota which are associated with Streptococcus pneumoniae (Spn)-induced pneumonia. So, we studied the therapeutic effect of SLBZS and evaluated whether gut microbiota is associated with the effects of SLBZS in improving Spn-induced pneumonia. Methods Spn-induced pneumonia NIH mice were treated by SLBZS and cefixime. A CT scan was performed and Myeloperoxidase (MPO) activity in lung homogenates was determined using the MPO Colorimetric Assay Kit. Inflammation levels in lung homogenates were measured using ELISA. Bacterial load was coated on a TSAII sheep blood agar. Intestinal gut microbiota information was analyzed according to sequencing libraries. Results SLBZS decreased bacterial load, reduced wet/dry weight ratio, inhibited myeloperoxidase activity, reduced the neutrophils count, and ameliorated lung injury. Furthermore, SLBZS inhibited interleukin (IL)-1β, IL-6, tumor necrosis factor-α, IL-2, IL-8, IL-12, and interferon-γ secretion and enhanced IL-10 secretion. These results suggest that SLBZS ameliorates lung injury in mice with Spn-induced pneumonia. Moreover, SLBZS reduced inflammatory cytokine levels in a concentration-dependent manner and increased gut microbiota abundance and diversity. After SLBZS treatment, bacteria such as Epsilonbacteraeota, Bacteroidetes, Actinobacteria, Proteobacteria, and Patescibacteria were significantly reduced, while Tenericutes and Firmicutes were significantly increased. Conclusion SLBZS ameliorates inflammation, lung injury, and gut microbiota in mice with S. pneumoniae-induced pneumonia.